What They're Reading - Inside the College Gates: How Class and Culture Matter in Higher Education. Issue 1 (2nd January 2016) - Andersen, Kent
Abstract: Stuber's Inside the College Gate examines how social class shapes student involvement in extracurricular activities during college, and in turn how student involvement shapes social class identity. The author's findings from a qualitative study of upper-middle-class and working-class students at a private liberal arts institution and a state flagship university provide administrators and student affairs practitioners with valuable insights on how best to reach out to working-class students. This review summarizes and contextualizes Stuber's findings.